Intelligently controlled solar-powered active fruit and vegetable dryer - Marebane, Ntwakgolo; N.Jiya, Immanuel; Gouws, Rupert (International Journal of Engineering and Technology, 2019)
Due to the impact of consecutive periods of drought recently being experienced in Africa; food storage and shelf life are decreasing rapidly. Food drying increases the shelf and storage life. Electrical dryers are expensive and electricity availability is a challenge in most African countries. To provide high quality and fast drying, a new intelligent automated active solar dryer is proposed in this paper. The dryer mainly operated on a battery system charged by photovoltaic panels. To produce heat in the oven, a heating element was used which was powered by a battery system. Sensors monitored the temperature, humidity and air velocity inside the dryer house and the data was send to a controller which performed automations on the switching of the convection fans and the heating element. The heating element switching was automated to optimise power consumption. Since the main energy source is solar radiation, a backup energy source was needed for worst case situations regarding weather. A port for electrical energy was installed for operations during cloudy and rainy days. From the results obtained, it was observed that the proposed system with temperature control, humidity control, forced hot air convection and forced humidity extraction offered an improved solution in comparison to the already available methods. These improvements observed are in terms of reduced energy usage, faster drying rate and preserved quality in the dried fruits.Â Â Â
Keywords: Food shortage; Solar powered dryer; Fruit; Vegetable; Intelligent control; Active dryer.